1999
DOI: 10.1177/000348949910800407
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery Improves Pulmonary Function in Patients with Asthma Associated with Chronic Sinusitis

Abstract: We evaluated the clinical efficacy of endonasal endoscopic sinus surgery (ESS) in patients with asthma associated with chronic sinusitis. Twenty-one patients (13 men and 8 women) from 27 to 72 years old were enrolled in this study. All patients had had sinus-related symptoms for more than 3 months and had computed tomographic evidence of paranasal sinus opacification. Fifteen patients underwent bilateral endonasal ESS under local anesthesia, and 6 other patients without surgery were controls. The sinus-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…For objective pulmonary functions after ESS, Dhong et al [25] and Manning et al [26] reported that the pulmonary function tests did not change. By contrast, Ikeda et al [27] found a significant improvement in peak expiratory flow of patients with asthma associated with chronic sinusitis following ESS, and Batra et al [28] recently found significant improvement in postoperative forced expiratory volume at 1 s and a reduction in systemic steroid usage.…”
Section: Discussionmentioning
confidence: 98%
“…For objective pulmonary functions after ESS, Dhong et al [25] and Manning et al [26] reported that the pulmonary function tests did not change. By contrast, Ikeda et al [27] found a significant improvement in peak expiratory flow of patients with asthma associated with chronic sinusitis following ESS, and Batra et al [28] recently found significant improvement in postoperative forced expiratory volume at 1 s and a reduction in systemic steroid usage.…”
Section: Discussionmentioning
confidence: 98%
“…856 Treatment of CRS decreases the severity of asthma (Table VIII-1). 319,861,862 Using objective and subjective sinonasal and asthma outcome measures, studies have demonstrated significant clinical improvement following ESS. 320,861,[863][864][865][866] In patients with asthma and NPs, ESS was shown to improve asthma severity scores, reduce the need of inhaled corticosteroids and reduce the frequency of asthma-related emergency room visits.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…1). After title and abstract screening, 43 articles were retrieved for full text screening, six of which met our inclusion criteria [11][12][13][14][15][16][17][18]. Cross-reference checking did not yield any extra eligible articles.…”
Section: Study Selectionmentioning
confidence: 99%
“…Ikeda et al [12] performed ESS on 15 patients (mean age 47 ± 14 years, range 27-72 years) with asthma and CRS. Six patients (mean age 42 years, range 32-64 years) who did not consent to ESS served as controls and were treated with topical corticosteroids alone.…”
Section: Study Characteristicsmentioning
confidence: 99%